Sustentabilidad hospitalaria, calidad y seguridad del paciente en el Hospital Clínico Universidad de Chile - Sakurada Z., Andrea; Mena V., Sandra; Salazar C., Carolina; Vidal C., Mario; Villaleiva C., Soledad; Quintana C., Magyolue (Revista Hospital Clínico Universidad de Chile, 2022)
The sustainability of the Universidad de Chile Clinical Hospital must be understood comprehensively; providing higher quality and safety for our patients, ensuring highest standards of medical care. The quality of care must be understood not only in complying with the minimum standards to accredit and grant GES benefits, establish agreements with health insurers and be financially competitive; It must be incorporated into its management the dimensions of quality - effectiveness, efficiency, accessibility, safety, equity and patientcentered care- minimizing the costs of non-quality work. Our Clinical Hospital, as our country’s main training center in healthcare professions, must include training at the undergraduate students’ curriculum in quality and patient safety issues.